Analysis of Air Temperature Distribution in a Closed House for Broiler in Wet Tropical Climate - A Yani; H Suhardiyanto; Erizal Erizal; BP Purwanto (Media Peternakan, 2014)
The objective of this research was to analyze the air temperature distribution in a closed house system for broiler in wet tropical climate by using computational fluid dynamics (CFD) to figure out the comfort level of the broiler in that system. The dimension of the experimental house was 100 m x 10 m x 2.4 m which could be occupied by 12,000 to 16,000 broiler chickens. The wall was made from expose mercy brick and curtain, plafond was made from galvanize, ventilation system used 6 fans with 1.27 m diameter and cooling pad and in-house lighting system used 60 units of 8 Watt lamps. The analysis of temperature distribution using CFD had high precision as was shown by the small number of average percentage of deviation (6.39%) between analyzed and measured results. Horizontally, the temperature distribution near the cooling pad was lower than others and continued to increase until near the position of the fan. In vertically, the air temperature in the area near the husks and the plafond were higher than the other mesurement points. At that height, the effective temperatures which were still comfort for the broiler were 20.07 oC, 19.81 oC and 20.04 oC at 12:20 h, 13:55 h and 15:20 h, respectively.